Segmentasi Wilayah Jawa Timur Berdasarkan Ketersediaan Fasilitas dan Tenaga Kesehatan - Kurniawan, Muhammad Erlangga; Ananta, Aditya Putra; Anugrah, Muhammad Cahya Raka; Damaliana, Aviolla Terza; Wara, Shindi Sheila May (ESTIMASI: Journal of Statistics and Its Application, 2026)
Health is a fundamental indicator in measuring societal well-being, where the equitable distribution of healthcare facilities and personnel plays a critical role. This study aims to segment regions in East Java Province based on the availability of healthcare facilities (community health centers, general/special hospitals, pharmacies, integrated health posts, and primary clinics) and healthcare personnel (doctors, midwives, nurses, pharmacists). The methods used include Principal Component Analysis (PCA) for dimensionality reduction, followed by K-Means and Agglomerative Hierarchical Clustering (AHC) algorithms using Average Linkage and Cosine Similarity. The analysis results show that AHC provides more optimal outcomes, with a silhouette score of 0.75, compared to K-Means which only achieved 0.51. The segmentation produced three main clusters: low (Pacitan, Ponorogo, Madura), medium (Bojonegoro, Jember, Banyuwangi), and high (Surabaya, Malang, Sidoarjo). These findings reveal disparities in the distribution of healthcare services in East Java and can serve as a foundation for more targeted policy formulation to improve equitable access to healthcare, particularly in underserved regions.